Government bond yields in Germany and Spain—empirical evidence from better days. Issue 5 (4th May 2018) - Basse, Tobias; Wegener, Christoph; Kunze, Frederik
Abstract : This paper tries to link the uncovered interest rate parity condition to the discussion about interest rate convergence in currency unions. Techniques of fractional cointegration analysis are used to examine the relationship between German and Spanish government bond yields with maturities of two, five, seven and ten years in the period 05 January 2001 to 29 December 2006. Back then (in the good times of the currency union) financial markets did not have to fear exchange rate risk and sovereign credit risk. Thus, the risk premia to be observed were small and driven by liquidity risk. Economic theory suggests that a cointegration vector of between the interest rates can only exist when markets do not expect exchange rate movements and the risk premium is not interest rate sensitive (or practically speaking the sensitivity is low). Given the data set examined here, it is probably no surprise that the interest rates of the two countries are cointegrated and that the cointegration vector of German and Spanish government bond yields with maturities of two, five and seven years seems to be . We then have also examined the degree of interest rate sensitivity of the yield spread between Spain and Germany. The differential between the yields of the two countries in all maturity brackets do not react to the level of interest rates in the currency union. This fits perfectly to our results with regard to the cointegration vector.